New Developments in International Research Collaboration - Hatakenaka, Sachi (International Higher Education, 2008)
International research collaboration has entered an era in which networking has a direct economic significance. Some governments are already beginning to pay a premium to become hubs in global excellence networks. The approaches include strengthening its bilateral ties, investing in world-class research center of excellence. The question is whether these developments will produce significant changes in the world's research capacity.